IMPROVEMENT OF SHORT DOUGH TECHNOLOGY USING GLUTEN-FREE RAW MATERIALS - Стукальська, Наталія; Полудньова, Катерина (SWorldJournal, 2025)
The study involved an analysis of modern scientific approaches to improving the technology of flour-based confectionery products, particularly shortcrust pastry, using unconventional raw materials. The inclusion of quinoa, red lentil, and amaranth flours